Digital humanities in the iSchool. (21st June 2021) - Walsh, John A.; Cobb, Peter J.; de Fremery, Wayne; Golub, Koraljka; Keah, Humphrey; Kim, Jeonghyun; Kiplang'at, Joseph; Liu, Ying‐Hsang; Mahony, Simon; Oh, Sam G.; Sula, Chris Alen; Underwood, Ted; et al.
Abstract: The interdisciplinary field known as digital humanities (DH) is represented in various forms in the teaching and research practiced in iSchools. Building on the work of an iSchools organization committee charged with exploring digital humanities curricula, we present findings from a series of related studies exploring aspects of DH teaching, education, and research in iSchools, often in collaboration with other units and disciplines. Through a survey of iSchool programs and an online DH course registry, we investigate the various education models for DH training found in iSchools, followed by a detailed look at DH courses and curricula, explored through analysis of course syllabi and course descriptions. We take a brief look at collaborative disciplines with which iSchools cooperate on DH research projects or in offering DH education. Next, we explore DH careers through an analysis of relevant job advertisements. Finally, we offer some observations about the management and administrative challenges and opportunities related to offering a new iSchool DH program. Our results provide a snapshot of the current state of digital humanities in iSchools which may usefully inform the design and evolution of new DH programs, degrees, and related initiatives.